A Pragmatic Study on Jouge Kankei among Japanese Native Speakers: Expressions of Reminder - Sanjaya, Sonda; Rosiah, Rosi (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2019)
This study aims at investigating the types and categorisation of conversation made by Japanese native speakers. The categorisation of the conversation is made based on vertical relationship (jouge kankei) from the pragmatics perspectives. Descriptive qualitative method is used to conduct the study. The participant of the study includes 14 Japanese native speakers working at Kyoto Minsai Japanese Language School and Palace Side Hotel who took part in role-plays. The results of the study indicate that there is no significant distinction of expressions made by (1) subordinates to their superiors, (2) among colleagues, and (3) from their superiors to their subordinates. These three groups also appear to use similar expressions when talking about promises and requests to borrow books. The distinction was found in expressions made by subordinates to their superiors. In the conversation made among colleagues and by superiors to subordinates, expressions to remind them to return some borrowed books were straightforwardly made. Meanwhile, these straightforward reminders were not found in conversations made by subordinates to their superiors. Additionally, the conversation among colleagues and made by superior to subordinates include expression of emphasizing requests; meanwhile, conversations made by subordinates to superiors do not. In addition, expressions of asking interlocutors’ conditions before reminding to return the book are made by colleagues to colleagues and subordinates to superiors and are not made by superiors to subordinates.